Bloom : the secrets of growing flowering houseplants year-round - Steinkopf, Lisa Eldred, 1966- (Cool Springs Press, 2022)
"Bloom is the only modern guide to cultivating flowering houseplants that includes insider secrets to encourage these beautiful plants to bloom and thrive"--